An intensive monitoring of adverse drug reactions in pediatric hospitalized patients of a tertiary care hospital - Patel, Prakruti P.; Makrani, Mustak M.; Gandhi, Anuradha M.; Desai, Mira K.; Desai, Chetna K. (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Children are at a higher risk of therapeutic failure due to major difference in pharmacokinetic, pharmacodynamics of drugs, off-label use and divergence of their illness from adult. The safety of drugs used in adult patients cannot be extrapolated to a pediatric age group. Hence, this study aimed to evaluate the incidence and overall pattern of adverse drug reactions in pediatric patients hospitalized in pediatric wards at a tertiary care hospital in India. Methods: Pediatric patients up to 12 years hospitalized in two randomly selected pediatric units were enrolled and followed up daily till discharge. Detailed information of patients and ADRs (adverse drug reactions) if any were recorded from case records. ADRs were assessed for incidence, onset, duration, management, outcome, causality, severity, preventability, seriousness and risk factors. Appropriateness of drug treatment in patients with ADRs was analyzed using Phadke’s criteria. Data was analyzed using student’s t test, ANOVA and Chi square test. Results: A total of 700 patients were enrolled (mean age 3.95±0.12 years). A total of 66 ADRs observed in 58 patients. Intravenous (70.4%) being most common route for ADRs. The incidence of ADRs was 8.28%. Majority of ADRs occurred within 1 day, commonly affected skin and appendages followed by (28.78%), GI (25.75%) ADRs were frequently associated with antimicrobials (69.38%) and vaccines and sera (12.24%). Majority of reactions were mild (56%%), non-serious (77.2%), not preventable (95.4%), recovered completely at discharge (83.33%) and had possible (77.2%) causal association with suspect drug. Age group 0-3 years and prescription of ≥5 drugs were risk factors for occurrence of ADRs. Semi rational drug therapy was observed in 65.5% patients. Conclusions: Clinicians should be vigilant regarding occurrence of ADRs in pediatrics especially during the first week of hospitalization. Risk factors like 0-3 years of age and multiple drugs should be taken into consideration during treatment of these patients to help minimize adverse drug reactions.